Nanoparticle ink‐based silicon Schottky diodes operating up to 2.84 GHz. Issue 6 (2nd October 2020) - Kühnel, Laura; Neumann, Kevin; Neises, Julian; Langer, Fabian; Erni, Daniel; Schmechel, Roland; Benson, Niels
Abstract: Today's printed, flexible electronics are often limited by the electronic performance enabled by the used functional semiconductor ink. Thin films from such inks typically exhibit a low charge carrier mobility, which inhibits high frequency device operation and limits their use for applications within the Internet‐of‐Things concept, such as wireless electronic tags and sensors. Our approach to overcome this issue is the use of printable silicon. The silicon is deposited using nanoparticle inks and is subsequently processed into self‐organized crystalline μ‐cone shaped structures using an excimer laser treatment. Due to the high crystallinity of the Si μ‐cones, they can be used for devices capable of high frequency operation. In this article, this is demonstrated on the example of a Schottky diode operating at switching speeds up to 2.84 GHz and thereby putting printable high frequency electronics within reach. Abstract : Printed, flexible electronics are an important part within the Internet‐of‐Things concept, due to the potential for high‐throughput and cost‐effective manufacturing. In line with this, a new type of Schottky diode based on a printable and laser modified silicon nanoparticle thin film is presented, which operates at switching speeds up to 2.84 GHz.